Etiology of gastrointestinal bleeding in patients on dual antiplatelet therapy. Issue 2 (15th March 2018) - Shaukat, Arslan; Waheed, Salman; Alexander, Ethan; Washko, Daniel; Dawn, Buddhadeb; Olyaee, Mojtaba; Gupta, Kamal
Abstract : OBJECTIVE: Dual antiplatelet therapy (DAPT) is associated with an increased risk of gastrointestinal (GI) bleeding and is thought to cause upper gastrointestinal bleeding (UGIB). However, recent reports indicate that the incidence of lower gastrointestinal bleeding (LGIB) in patients on DAPT may be increasing. We aimed to compare the endoscopic findings and etiology of GI bleeding between patients on DAPT compared with those not on DAPT. METHODS: This was a retrospective, single‐center, case‐control study. Cases were 114 consecutive patients admitted with a first episode of GI bleeding while on DAPT who underwent detailed GI evaluation. We chose 114 controls who had GIB but were not on DAPT. RESULTS: There was no significant difference in the incidence of UGIB or LGIB between the two groups (UGIB: 53.5% vs 51.3% and LGIB: 46.5% vs 48.7%, P = 0.10) or within groups (DAPT: 53.5% vs 46.5%, P = 0.30 and controls: 51.3% vs 48.7%, P = 0.80). Although the DAPT group had a lower prevalence of the usual UGIB risk factors, it had a higher likelihood of bleeding from varices or upper GI inflammation [odds ratio (OR) 3.54, 95% confidence interval (CI) 0.14–92.3; OR 13.98, 95% CI 1.40–140.36]. No etiology of bleeding was identified in a higher percentage of patients on DAPT than those who were not (22.8% vs 5.3%). CONCLUSION: In patients with GI bleeding, the incidences of UGIB and LGIB are similar irrespective of their DAPT use.